Complete mitochondrial genome of Anarta trifolii (Lepidoptera: Noctuidae) - Yu-Peng Wu; Jun-Jiao Lu; Jing Yang; Ju-Ping Wang; Tian-Wen Cao; Ren-Jun Fan (Mitochondrial DNA. Part B. Resources, 2020)
The Anarta trifolii belongs to Noctuidae in Lepidoptera. The complete mitogenome of A. trifolii was described in this study, which is typical circular duplex molecules and 15,281 bp in length, containing the standard metazoan set of 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and an A + T-rich region. The gene order is same with other lepidopterans. Except for cox1 started with CGA, all other PCGs started with the standard ATN codons. Most of the PCGs terminated with the stop codon TAA, whereas nad3 is TAG, nad4 has the incomplete stop codon T. The phylogenetic tree showed that A. trifolii and other three species belong to Hadeninae, which are clustered into a clade.